2017
DOI: 10.1111/acer.13471
|View full text |Cite
|
Sign up to set email alerts
|

Cut-Point Levels of Phosphatidylethanol to Identify Alcohol Misuse in a Mixed Cohort Including Critically Ill Patients

Abstract: Background Although alcohol misuse is associated with deleterious outcomes in critically ill patients, its detection by either self-report or examination of biomarkers is difficult to obtain consistently. Phosphatidylethanol (PEth) is a direct alcohol biomarker that can characterize alcohol consumption patterns; however, its diagnostic accuracy in identifying misuse in critically ill patients is unknown. Methods PEth values were obtained in a mixed cohort comprised of 122 individuals from medical and burn in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 48 publications
(68 reference statements)
3
50
0
1
Order By: Relevance
“…PEth is formed from PC present in the erythrocyte cell membrane, and previous studies have shown a positive correlation between reported alcohol consumption and PEth concentration in blood (Aradottir et al., ; Stewart et al., ; Walther et al., ). Likewise, drinking studies in volunteer subjects with single or several intakes of alcohol sometimes aiming at specified targets of blood alcohol concentration have shown a correlation between PEth and consumed amounts of alcohol (Gnann et al., ; Kechagias et al., ; Schrock et al., ) but with significant interindividual differences in PEth values in relation to alcohol consumption (Afshar et al., ; Aradottir et al., ; Gnann et al., ; Kechagias et al., ; Schrock et al., ; Walther et al., ). Possible reasons for the observed between‐individual variability (e.g., variation in PC concentration, in PLD activity, or in the formation and elimination of PEth, and a possible lack of reliability in reported consumption) have been discussed in a previously published paper (Hahn et al., ).…”
mentioning
confidence: 99%
“…PEth is formed from PC present in the erythrocyte cell membrane, and previous studies have shown a positive correlation between reported alcohol consumption and PEth concentration in blood (Aradottir et al., ; Stewart et al., ; Walther et al., ). Likewise, drinking studies in volunteer subjects with single or several intakes of alcohol sometimes aiming at specified targets of blood alcohol concentration have shown a correlation between PEth and consumed amounts of alcohol (Gnann et al., ; Kechagias et al., ; Schrock et al., ) but with significant interindividual differences in PEth values in relation to alcohol consumption (Afshar et al., ; Aradottir et al., ; Gnann et al., ; Kechagias et al., ; Schrock et al., ; Walther et al., ). Possible reasons for the observed between‐individual variability (e.g., variation in PC concentration, in PLD activity, or in the formation and elimination of PEth, and a possible lack of reliability in reported consumption) have been discussed in a previously published paper (Hahn et al., ).…”
mentioning
confidence: 99%
“…However, when compared to a critically ill patient with lower Hb (100 g/l) and Hct (0.3), a typical male adult can have a significantly different red cell profile with this difference being potentially up to 50% (Hb g/l: 154/100 = 1.54 [+54%]; Hct: 0.455/0.3 = 1.52 [+52%]). Hence, in the context of Afshar and colleagues' () study, the impact of reduced red cell volume in critically ill patients can affect the PEth values.…”
mentioning
confidence: 97%
“…In this letter, we briefly discuss the findings by Afshar and colleagues () regarding the use of the alcohol biomarker phosphatidylethanol (PEth) to identify alcohol misuse in a mixed cohort of individuals, particularly in critically ill patients from an intensive care unit (ICU). This particular patient group as highlighted by the authors is a difficult cohort to test for the presence of an alcohol use disorder and has therefore been underresearched.…”
mentioning
confidence: 99%
See 2 more Smart Citations